Ivy: a parallel simulator for variable structure systems under multi-core environments. (1st January 2013) - Yang, Chen; Li, Bo Hu; Chai, Xudong; Chi, Peng
Simulation is widely applied in more challenging problems, while multi-core processors are increasingly pervasive. An advanced parallel simulator under multi-core environments called Ivy was proposed in order to enhance the ability to simulate variable structure systems and improve the performance of large-scale simulation. It can: 1) support dynamic structure of the simulation system using flexible models with alterable ports, unified event passing management, object management and system runtime controller, while leading almost no interruption to the simulation execution; 2) increase parallelism of model execution by parallel computation of models' lower bound on time stamp (LBTS); 3) achieve high efficiency of parallel execution using multi-threads and shared variables inside an operating system process (OSP). One application example was presented, which validated high efficient parallelism of system execution and variable structure capability of the simulation system using our proposed simulator.